2008
DOI: 10.1099/mic.0.2008/020784-0
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial activity of Cyt1Aa from Bacillus thuringiensis subsp. israelensis

Abstract: Cyt1Aa is a d-endotoxin protein that is produced by Bacillus thuringiensis subsp. israelensis. It is a membrane pore-forming toxin that is lethal to insect larvae and is broadly cytolytic to vertebrate as well as invertebrate cells. Cyt1Aa is produced as a protoxin of 27 kDa. Proteolytic activation results in a reduction of the molecular mass to approximately 23-24 kDa and a threefold increase in activity. In this research, Cyt1Aa crystals were purified from B. thuringiensis IPS78/11 harbouring the expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 42 publications
(36 reference statements)
0
14
0
Order By: Relevance
“…In vitro processing of Cyt1Aa protoxin yields single active 22–25 kDa fragment [136,137] that is about three times more effective than the protoxin [138,139]. …”
Section: δ-Endotoxins Of Btimentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro processing of Cyt1Aa protoxin yields single active 22–25 kDa fragment [136,137] that is about three times more effective than the protoxin [138,139]. …”
Section: δ-Endotoxins Of Btimentioning
confidence: 99%
“…Cyt1Aa, Cry4Ba and Cry11Aa, as well as two proteins (of 36 and 34 kDa) isolated from Bti , are antibacterial also exogenously, against E. coli and Gram-positive species ( Micrococcus luteus, Streptomyces chrysomallus and Staphyloccocus aureus ) [137,166,167]. Cyt1Aa is bactericidal for E. coli , whereas it is bacteriostatic for S. aureus as reflected in morphological changes and ion balance alteration [137].…”
Section: Antibacterial and Anticancer Activities Of Bti δ-Endotoxinsmentioning
confidence: 99%
“…Though different peptides kill pathogens by different mechanisms, their cationic and amphipathic nature allows them to interact with negatively charged microbial membranes (3,6,11,26). Microbial membrane interaction with such peptides leads to several events, such as (i) formation of multimeric pores in the lipid bilayer of the cell membrane (11,44), (ii) loss of ionic balance (7), and (iii) interaction with DNA or RNA (4,5,30,37), all eventually resulting in cell death. Their broad-spectrum activity and unique mode of action and the fact that resistance against host defense antimicrobial peptides is very unlikely to develop make them promising candidates for a new class of antibiotics (35,45).…”
mentioning
confidence: 99%
“…The Cry and Cyt proteins toxins of B. thuringiensis have different activities including; antimicrobial (Cahan et al, 2008), insecticidal (Höfte and Whiteley, 1989), toxicity against nematode (Wei et al, 2003), antitumoral, (Chan et al, 2012;Jung et al, 2007) and adjuvant of the immune system (Román Calderón et al, 2007). B. thuringiensis spore crystals have shown toxicity for lymphocytes and promoting cytotoxic and genotoxic effects for the erythroid lineage of bone marrow at high concentrations which is not commonly found in the environment, indicated that these B. thuringiensis spore crystals (Mezzomo et al, 2015) were not harmless to mammals (Mezzomo et al, 2015;Okumura et al, 2014).…”
Section: Introductionmentioning
confidence: 99%